IMPLEMENTASI PRINSIP GOOD GOVERNANCE DALAM PEMERINTAHAN DESA UNTUK MENCEGAH PENYALAHGUNAAN DANA DESA - -, Citranu (Belom Bahadat, 2022)
The purpose of this paper is to find out the application of good governance principles in village government. This paper uses a normative legal research method, namely by applying a statutory and conceptual approach. The legal source used are primary legal source, secondary legal source and tertiary legal source. Analysis of legal source using descriptive analysis. The result of this paper is that the implementation of authority in the village government must be based on the principle of good governance which pays attention to legal certainty, expediency and justice in order to achieve the ideals of the state in the welfare of the people